2020
DOI: 10.1590/s1980-6574202000020077
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors and profile of injuries in professional ballroom dancers in Brazil: a cross-sectional study

Abstract: Ballroom dance consists of a modality characterized by fast and dynamic movements performed in pairs, aiming at technical and artistic excellence. Objective: To analyze the prevalence, characteristics, and factors associated with injuries in professional ballroom dancers, considering possible differences between sexes. Method: 320 professional dancers of both sexes with a mean age of 31.48±8.63 years, who were in professional companies and/ or dance schools from five regions of Brazil. The measurement was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The present study revealed that males experience a higher rate of injuries during dancing which might have arisen from factors such as lack of experience than females, using more vigorous movements, performing fewer warm-up and cool-down exercises, lengthy practice sessions per day than females, having brief breaks between two dancing sessions, and practicing at a faster pace than female dancers. These findings are compatible with the studies conducted on Ballet dancers and Ballroom dancers that found high injury rate among the male dancers [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that males experience a higher rate of injuries during dancing which might have arisen from factors such as lack of experience than females, using more vigorous movements, performing fewer warm-up and cool-down exercises, lengthy practice sessions per day than females, having brief breaks between two dancing sessions, and practicing at a faster pace than female dancers. These findings are compatible with the studies conducted on Ballet dancers and Ballroom dancers that found high injury rate among the male dancers [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Dance involves beautiful and complex mechanical and performative actions that require discipline, technique, and various physical abilities, using movement as a fundamental element expressed at a technical and artistic level 1,2 . Ballroom dancing, known as social dance for being danced by peers, is also practiced as a physical-motor activity that develops skills practice of physical, cognitive, social, and cultural habilities that bring benefits to the life and health of its various adherents [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the responsibility of planning and giving practical classes to regular classes at different times, his routine includes choreographic creations, rehearsals, performance presentations, extra-class courses, private classes at unconventional times, and parties inside and outside the linked 6 . Factors that make the professional routine stressful, with an exhausting workload and that can negatively influence general health and the presence of fatigue 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of studies on Brazilian cheerleaders, if we consider modalities that present a similar movement pattern, we can indicate the national panorama. Brazilian studies have already established a high frequency of injuries in dancers and gymnasts [13][14][15] . While athletes in artistic gymnastics had a high prevalence of injuries in the upper limbs (especially the wrist and shoulder), ballet dancers, ballroom dancers, and trampoline gymnasts had more injuries in the lower limbs.…”
Section: Introductionmentioning
confidence: 99%
“…While athletes in artistic gymnastics had a high prevalence of injuries in the upper limbs (especially the wrist and shoulder), ballet dancers, ballroom dancers, and trampoline gymnasts had more injuries in the lower limbs. Ankle sprains stand out with an occurrence of 25.9% to 67.6% having been reported [13][14][15] . One of the differences that can be highlighted between these modalities is that in artistic gymnastics there is a high frequency of weight-bearing in the upper limbs.…”
Section: Introductionmentioning
confidence: 99%